2018
DOI: 10.12659/msm.905826
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived and Amniotic Fluid-Derived Stem Cells: A Preliminary In Vitro Study Comparing Myogenic Differentiation Capability

Abstract: BackgroundAround the world, disabilities due to musculoskeletal disorders have increased and are a major health problem worldwide. In recent years, stem cells have been considered to be powerful tools for musculoskeletal tissue engineering. Human adipose-derived stem cells (hADSCs) and amniotic fluid-derived stem cells (hAFSCs) undergo typical differentiation process into cells of mesodermal origin and can be used to treat muscular system diseases. The aim of the present study was to compare the biological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Similarly, a comparative study revealed that adMSC expressed significantly more cardiomyocyte specific biomarkers as DFSCs following cardiac programming with cytokine supplemented culture medium [11]. The impact of MSC origin on programming capability was also shown for non-cardiac cell lineages like hepatocytes and smooth muscle cells [59,62].…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, a comparative study revealed that adMSC expressed significantly more cardiomyocyte specific biomarkers as DFSCs following cardiac programming with cytokine supplemented culture medium [11]. The impact of MSC origin on programming capability was also shown for non-cardiac cell lineages like hepatocytes and smooth muscle cells [59,62].…”
Section: Discussionmentioning
confidence: 89%
“…Another cell population used in skeletal muscle TE is mesenchymal stem cells (MSCs). MSCs are multipotent progenitor cells that are found in the stroma of various tissue types (e.g., umbilical cord, adipose tissue) and can differentiate into multiple cell lineages of the mesodermal lineage, including adipocytes, osteoblasts, chondrocytes, or myocytes [33][34][35]. The most commonly used tissues for the isolation of MSCs are bone marrow (BMSCs) and adipose tissue (ADSCs).…”
Section: Cellular Aspects Of Skeletal Muscle Tementioning
confidence: 99%
“…Moreover, these cells exhibited properties of MSCs, such as multilineage differentiation potential towards fibroblasts, adipocytes, osteocytes [ 265 ], and chondrogenic lineage [ 266 ]. Ovine mesenchymal amniocytes were shown to give rise to smooth and skeletal muscle cells after the treatment with promyogenic medium, which resulted in expression of transgelin, calponin, and α-actin [ 267 ].…”
Section: Signaling Pathways Involved In Fetal-derived Msc Development and Differentiationmentioning
confidence: 99%